Application of Cyberlindnera fabianii isolate as a potential starter culture in type IV sourdough to improve techno-functional capabilities of barley bread - Alireza Sadeghi; Fahimeh Hajinia; Hossein Purabdolah; Maryam Ebrahimi; Sara Shahryari; Maryam Pahlavani (Journal of Agriculture and Food Research)
Indigenous sourdough (SD) yeasts have promising potential applications as starter culture in processing of the baked goods. In the present study, techno-functional capabilities of the predominant yeasts isolated from barley SD were characterized to select a proper starter culture for type IV SD. Accordingly, techno-functional characteristics of the produced barley bread including textural features using a texture analyzer, sensory properties through evaluation of the panelist's scores, mold-free shelf-life using a challenge test, and their antioxidant capacity based on the DPPH free radical scavenging activity were compared to each other. According to the results, crumb hardness of the barley bread produced with BSY 3 isolate was significantly (P < 0.05) lower than those of the other samples. This bread also showed the highest crumb porosity (14.20 %). In addition, methanolic and water-salt soluble extracts of the aforementioned sample had the highest ability to scavenge DPPH free radical (equal to 87.75 % and 32.65 %, respectively). Although the surface growth of Aspergillus niger on the produced samples was significantly higher than that of the control sample containing baker's yeast, while SD breads showed higher mold-free shelf-life. Furthermore, there was no significant difference among the produced samples in terms of the overall acceptability. Based on the sequencing results of the PCR products, the selected yeast isolate was also identified as Cyberlindnera fabianii. Accordingly, the yeast isolate can be used as starter culture in type IV SD with the aim of improving the quality characteristics of the produced barley bread.